Pendant in the Jewelry Fashion of the Northern Renaissance and Mannerism - Romanenkova, Julia; Kuzmenko, Halyna; Bratus, Ivan (Journal of History Culture and Art Research, 2019)
The main objective of the study is to highlight the role of pendants in the general context of the jewelry art of the Northern Renaissance and Mannerism, the reasons for the popularization of this type of jewelry and offer a version of their classification. The methodological basis of the study is the application of iconological method of art history analysis to characterize the array of jewelry in the general context of artistic culture of the Renaissance and Mannerism of the countries, located north of the Alps; the historical method — to characterize the jewelry works in a certain chronological sequence, mainly — created in the secondhalf of 16thand beginning of 17thcenturies; comparative method — to compare the stylistic features of jewelry of different countries of Europe and track their transformation over time. The scientific novelty of the study is in the fact that pendants of Northern Renaissance and Mannerism as the most popular type of personal jewelry have never been considered as an object of serious scientific interest, they were characterized previously in general context of arts and crafts of this period. Therefore, this essay attempts to show pendants as an independent phenomenon, a segment of jewelry fashion of the 16thand early 17th centuries in the Ukrainian science of art. The article makes an excursion into the European jewelry of the 16th century, outlines the types of jewelry in demand during this period, shows their main stylistic features. The materials and techniques preferred by the experts of Northern Europe in the 16th and early 17th centuries, the main subjects and ornamental motifs which existed in the decoration of jewelry, the reasons for their popularization are highlighted. A variant of the classification of pendants of this epoch is proposed, in which the dominant motif of the décor is chosen as the main criterion. The characteristics of individual pendants created during the Renaissance and Mannerism in Spain, the Netherlands, England, Germany, France. Data is collected from the collections of the State Hermitage in St. Petersburg, the Art Institute of Chicago, Victoria and Albert Museum and British Museum in London.